(untitled) (Revista científica Olimpia, 2020)
Various studies and investigations have revealed that the teaching staff of Physical Education keeps on falling for the tuitional traditional styles without attending to aspects related with the very educational contents, the evaluation, the context and the motivation of the student for the process of teaching learning (Méndez, 2009). Kirk (2005) regards the model as the main shaft of teaching be more than enough the that to construct the didactic programming of the area of Physical Education. They expose the different kinds of models for the sports teaching through physical education and his various options with educational interests in this article, the integrative model is up for like proposal the teaching of the technique of the soccer in the school physical education, as well as the initial actions to the technique for the development of the abilities of this sports.